Taking a stance: two vignettes in Lucretius's De rerum natura and Seneca's Troades - Winter, Kathrin (TAPA, 2019)
The famous shipwreck episode at the beginning of Lucretius’s book 2 and the last choral ode in Seneca’s Troades are examples of the “vignette,” i.e., a spatially vivid scene that achieves its vivid effect through an appeal to corporeal experience. The literary technique applied here relies on the recipient’s knowledge of her physical capabilities and her body’s sensorimotor system and can be described with approaches from cognitive studies. This article argues that both passages use the vignette as a means to convey a fixed point of perception within an imagined environment to reflect on proper comportment in a disastrous situation.